Threat-balancing in vendor transition - CHUA, Cecil Eng Huang (Institutional Knowledge at Singapore Management University, 2008)
While many outsourcing contracts are expiring, and vendor transition is becoming an increasing concern, little research helps organizations manage vendor transition. This paper explores vendor transition across two case sites. In one case, the outgoing vendor cooperated with the client which resulted in the client distancing itself from interactions between vendors. In the second case, the outgoing vendor was openly hostile, with the result that the client allied with the incoming vendor to manage vendor transition. These findings mirror expectations from balance of threat theory, a political science theory about interactions between nations. Balance of threat theory predicts that outgoing vendor hostility and the capability of the client to mitigate hostility determine whether a client takes a hard or soft balancing strategy during vendor transition.